2008
DOI: 10.1080/00050060802413354
|View full text |Cite
|
Sign up to set email alerts
|

Psychology training clinics in Australia and New Zealand: Clinic structure

Abstract: Psychology clinics play a central role in training clinical psychologists. Surprisingly little empirical research has examined the structure or operations of clinics. A survey of directors of clinical training, and psychology clinic directors in Australia and New Zealand is presented. Clinics in this region vary enormously in size, throughput and staffing levels. They range from being fully funded by their university to being entirely funded out of their external income stream. Clinic-clinical program relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Regular evaluation of clinical outcomes linked to trainee psychologist performance will increase the credibility of the field of clinical psychology and training in university clinics. It is suggested that this practice is likely to increase the profile of and improve standards for accreditation purposes in clinical psychology training programmes (Babbage, ; Gonsalvez et al, ). The current evaluation of client profiles, disorder types, and effectiveness of therapy will provide comparable information for future research of its kind on university‐based clinics in Australia (Murrell et al, ).…”
Section: Aimsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regular evaluation of clinical outcomes linked to trainee psychologist performance will increase the credibility of the field of clinical psychology and training in university clinics. It is suggested that this practice is likely to increase the profile of and improve standards for accreditation purposes in clinical psychology training programmes (Babbage, ; Gonsalvez et al, ). The current evaluation of client profiles, disorder types, and effectiveness of therapy will provide comparable information for future research of its kind on university‐based clinics in Australia (Murrell et al, ).…”
Section: Aimsmentioning
confidence: 99%
“…Few published studies from university‐based clinic settings have evaluated clinical outcomes to determine effectiveness of therapy. Prior research has focussed on the effectiveness of training and clinic structure (Babbage, ; Gonsalvez et al, ).…”
Section: Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the productions that are directly aimed toward the consideration of specific moments in the academic development of psychologists, it is worth remembering those of Babbage (2008), Gonsalvez, Hyde, Lancaster and Barrington (2008) and Lewis, Hatcher and Pate (2005), which rigorously addressed the importance of the university clinic and the supervision in the professional development of psychologists. We also highlight the studies of Aguirre et al (2000), Aiello-Vaisberg (1999) and Moratto (1989) who, from different methodological perspectives, presented pedagogical proposals to deal with the affective-emotional aspects of the students that emerge in the first contacts with patients.…”
mentioning
confidence: 99%